Effects of Thai Chi exercises, and laughter therapy on active aging in community-dwelling older adults: A systematic review. - Bibi, Rashida; Yan, Zhang; Aurang Zeb (International Journal of Endorsing Health Science Research, 2022)
Background: Community-dwelling older adults lack opportunities for health care, health-related knowledge, participation in health care activities, and a sense of security. These all are some of the identified hindrances on Active-aging elderly living in the community. This study explores the fundamental elements of long-distance Happy-age education in terms of Active-aging in older adults living in the community. Methodology: An extensive literature search returned 443 studies. Of these, only 10 studies met the inclusion criteria of a scientific investigation of the effectiveness of long-distance Happy age education programs, including fun exercise and laughter that contain appropriate elaboration on theoretical constructs and methods. Results: The qualitative assessment resulted that programs containing more fun-based interventions are effective regardless of the type of intervention. The effectiveness is also modulated by other variables such as the participant's education level, gender, current health status, and financial constraints. Conclusion: This review suggests that the level of the community-dwelling older adults have seemed to benefit from Thai Chi Rhythmic exercises and laughter exercises. More studies of this topic with older adult populations are needed to select the most convenient Happy-age education program that can improve the level of Active-aging and prolong life with happiness can be fulfilled.